KESEJAHTERAAN PSIKOLOGIS MAHASISWA SEMESTER AKHIR IAIN SURAKARTA DI TENGAH PANDEMI COVID-19 - Isdiyah Isdiyah; Ernawati Ernawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The pandemic has brought changes so wide in Indonesia, and also for the students psychological well-being. This research aims to describe psychological well-beingÂ the final year students of IAIN Surakarta. The research method used a qualitative method. Informants the research were 10 studentÂ semester 9. Technique of analyzing data through data reduction,Â data presentation and conclusion. The results showed the psychological well-being of students in the midst of Covid-19 pandemic was good, some was not good. Students who have good psychological well-being, are shown by having environmental mastery, autonomy, life goals, personal growth, self-acceptance, positive relationships with family, friends, and their supervisors. Subjects can be grateful for situation and take advantage of all limitations. Students who have poor psychological well-being tend to be often anxious, afraid, lazy and resigned to their situation without being accompanied by efforts to be productive, and unable to develop themselves in the midst of Covid-19 pandemic.